KONSEKUENSI YURIDIS SALINAN AKTA NOTARIS YANG TIDAK SAMA BUNYINYA DENGAN MINUTA AKTA TERHADAP KEABSAHAN PERJANJIAN - Dedy Prasetyo Winarno (Arena Hukum, 2015)
AbstractThe provisions of Article 16 paragraph (1) letter d of Law No. 2 of 2014 states that a copy of the certificate issued by the minutes deed, Article 1 point 9 of Law No. 2 of 2014 on the copy of the certificate, which is a copy of the verbatim of the entire deed on the bottom copy of the deed listed The phrase